2022
DOI: 10.1038/s41598-022-06128-4
|View full text |Cite|
|
Sign up to set email alerts
|

Occurrence of plasmid-mediated quinolone resistance genes in Pseudomonas aeruginosa strains isolated from clinical specimens in southwest Iran: a multicentral study

Abstract: This study aimed to assess the presence of qnrA, qnrB, qnrC, qnrD, qnrS, qepA, and aac(6′)-Ib-cr determinants as well as quinolone resistance pattern of clinical isolates of P. aeruginosa in Ahvaz, southwest Iran. A total of 185 clinical isolates of P. aeruginosa were collected from 5 university-affiliated hospitals in Ahvaz, southwest Iran. The disk diffusion method was applied to assess the quinolone resistance pattern. The presence of qnrA, qnrB, qnrC, qnrD, qnrS, qepA, and aac(6′)-Ib-cr genes was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…In this study, PDC β-lactamase and OXA β-lactamase genes were prevalent in collected strains, which can induce multidrug resistance to some extent by antibiotic inactivation. Previous studies showed that the presence of qnrVC genes plays important roles in quinolone resistance (Liu et al, 2018;Saki et al, 2022), and 2.3% of collected Heat map showing the resistance genes for the collected P. aeruginosa high-risk clone strains. The heat map was formed by performing tblastn searches using the sequences present on the Comprehensive Antibiotic Resistance Database (CARD) as queries and the genomes as subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PDC β-lactamase and OXA β-lactamase genes were prevalent in collected strains, which can induce multidrug resistance to some extent by antibiotic inactivation. Previous studies showed that the presence of qnrVC genes plays important roles in quinolone resistance (Liu et al, 2018;Saki et al, 2022), and 2.3% of collected Heat map showing the resistance genes for the collected P. aeruginosa high-risk clone strains. The heat map was formed by performing tblastn searches using the sequences present on the Comprehensive Antibiotic Resistance Database (CARD) as queries and the genomes as subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently several studies have reported the presence of qnr genes in P. aeruginosa. Saki et al (2022) from Iran reported the findings of qnr B, A and S in 29%, 25% and 20% of isolates, respectively. From saudi, qnr D, S and AAC(6)-Ib-cr were found in 79%, 79% and 71% of P. aeruginosa; the other study from India showed that 78% of isolates had aac(6′)-Ib-cr, 14% of isolates harbored qnrB and qnrS, 10% had both qnrB and qnrS and 3% oqxAB gene (El-Badawy et al, 2019;Geetha et al, 2022).…”
Section: Plasmid-mediated Quinolone Resistancementioning
confidence: 98%
“…The compounds in this class inhibit two bacterial enzymes that play an essential role in bacterial DNA synthesis. Resistance to quinolones is recognized as a shared mechanism contributing to resistance in Gram-negative bacilli such as E. coli and P. aeruginosa through protein modification (Abdel-Rhman et al, 2021 ; Saki et al, 2022 ). Sulfonamides are one of the oldest types of antibiotics that belong to the class of synthetic antimicrobial agents.…”
Section: Emergence Of Antibiotic Resistancementioning
confidence: 99%